Unveiling the evolutionary state of three B supergiant stars: PU Gem, ϵ CMa, and η CMa - Sánchez Arias, Julieta Paz (2023)
We aim to combine asteroseismology, spectroscopy, and evolutionary models to establisha comprehensive picture of the evolution of Galactic blue supergiant stars (BSG). To start such aninvestigation, we selected three BSG candidates for our analysis: HD 42087 (PU Gem), HD 52089(e CMa), and HD 58350 (η CMa). These stars show pulsations and were suspected to be in anevolutionary stage either preceding or succeding the red supergiant (RSG) stage. For our analysis,we utilized the 2-min cadence TESS data to study the photometric variability, and we obtained newspectroscopic observations at the CASLEO observatory. We used non-LTE radiative transfer modelscalculated with CMFGEN to derive their stellar and wind parameters. For the fitting procedure,we included CMFGEN models in the iterative spectral analysis pipeline XTGRID to determine theirCNO abundances. The spectral modeling was limited to changing only the effective temperature,surface gravity, CNO abundances, and mass-loss rates. Finally, we compared the derived metalabundances with prediction from Geneva stellar evolution models. The frequency spectra of all threestars show stochastic oscillations and indications of one nonradial strange mode, fr = 0.09321 d−1inHD 42087 and a rotational splitting centred in f2 = 0.36366 d−1in HD 52089. We conclude that therather short sectoral observing windows of TESS prevent establishing a reliable mode identificationof low frequencies connected to mass-loss variabilities. The spectral analysis confirmed gradualchanges in the mass-loss rates, and the derived CNO abundances comply with the values reportedin the literature. We were able to achieve a quantitative match with stellar evolution models for thestellar masses and luminosities. However, the spectroscopic surface abundances turned out to beinconsistent with the theoretical predictions. The stars show N enrichment, typical for CNO cycleprocessed material, but the abundance ratios did not reflect the associated levels of C and O depletion.We found HD 42087 to be the most consistent with a pre-RSG evolutionary stage, HD 58350 is mostlikely in a post-RSG evolution and HD 52089 shows stellar parameters compatible with a star atthe TAMS.